2011
DOI: 10.1007/s00520-011-1133-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of the general practitioner during the active breast cancer treatment phase: an analysis of health care use

Abstract: PurposeLittle is known about the actual involvement of the general practitioner (GP) during the active breast cancer treatment phase. Therefore, this study explored (disease-specific) primary health care use among women undergoing active treatment for breast cancer compared with women without breast cancer.MethodsA total of 185 women with a first diagnosis of early-stage breast cancer between 1998 and 2007 were identified in the primary care database of the Registration Network Groningen and matched with a ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
35
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 25 publications
8
35
1
1
Order By: Relevance
“…Moreover, healthcare use of CRC patients in primary care during treatment has not yet been studied. In a Dutch study on patients with breast cancer, increased contact rates with the GP were observed in the first year after diagnosis when compared with a reference population [12]. Similar findings were reported in a study conducted in Denmark concerning all cancer types [13], but the reasons associated with health care use were not examined in this study.…”
Section: Introductionsupporting
confidence: 79%
“…Moreover, healthcare use of CRC patients in primary care during treatment has not yet been studied. In a Dutch study on patients with breast cancer, increased contact rates with the GP were observed in the first year after diagnosis when compared with a reference population [12]. Similar findings were reported in a study conducted in Denmark concerning all cancer types [13], but the reasons associated with health care use were not examined in this study.…”
Section: Introductionsupporting
confidence: 79%
“…A major strength of the present study is the use of a primary care database to analyse healthcare utilisation rates among women with a history of breast cancer and women without breast cancer from the same population [20]. As the presentation of health problems was recorded by GPs, our study is much less prone to recall or non-response bias than surveys with self-reported data on healthcare use [36].…”
Section: Discussionmentioning
confidence: 99%
“…Face-to-face contacts included consultations in general practice and home visits carried out by GPs and other general practice workers [20]. Observation time was calculated as time since matching date until the endpoints (e.g., breast cancer recurrence, death, and departure) ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations